Improving Students Learning Approach in Mathematical Thinking through Constructivist Learning Approach with Creativity for Architecture Students - Samsudin, Nor Syamimi; Samsuddin, Prof. Madya Dr.Ismail; Yusof, Ahmad Faisol; Mohd Zaki, Mohd Zikri (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2018)
The purpose of this research is to measure the effectiveness of constructivist learning approach in structural study specifically for architecture students. Theoretically, improving student’s performance in mathematics is challenging for today education. In architectural education, structural study is part of the non- design courses in the syllabus under the area of technology and environment and it involve in mathematical calculations. In the context of typical classrooms that adopt conventional teaching method, students are usually taught using structured rules based on the given academic syllabus. However, teaching architecture students need a different approach. This is because architecture students learn by understanding the application into practice rather than by only solving the principleproblem. Purposive sampling which is the Torrance Test of Creative Thinking (TTCT) was selected as the method of the study and teaching experiment was conducted. In the experimental structural design, 26 groups of architecture students were tested based on two situations; pre-test (original) and post-test (change), and tests are conducted according to the stages and times set for each topic. The experiment was designed based on the Constructivist learning approach as foundation of the experiment to study the mathematical creativity of the students. The findings show that there are positive impacts on creativity in the subject of structural study which beneficially affects their understanding and application abilities. Further research needs to done to ensure this beneficial outcome can be greatly support students’ long-term retention of knowledge and skills. Keywords: Constructivist learning approach, Creativity in mathematical thinking, and Experimental study for architecture students